Hubungan Antara Media Pembelajaran dan Minat Belajar Fisika: Studi Kasus pada Fluida Statis - Ramdani, Gifar; Nursabila, Nursabila (Jurnal Pendidikan dan Ilmu Fisika, 2024)
This study aims to analyze the relationship between the use of learning media and students' interest in physics, particularly in static fluid topics. The research employed a qualitative method with a case study approach involving 11th-grade students at a private high school in Garut. Data were collected through questionnaires, observations, and document studies, then analyzed using Miles and Huberman's qualitative data analysis techniques. The findings indicate that the average student interest in learning physics is relatively low, at 39.3%. The highest-rated indicator is "learning media facilitates understanding" (82%), while the lowest-rated is "having supplementary books" (11%). These findings highlight the significant role of interactive learning media in enhancing students' comprehension and engagement. However, students' learning habits, such as the lack of supplementary books and low assignment completion rates, require more attention. The study concludes that innovative learning media should be integrated with efforts to strengthen students' learning habits to holistically improve their interest in learning. Support from teachers, parents, and the school environment is essential in creating engaging and effective learning experiences, thereby motivating students to study physics.